2021
DOI: 10.1186/s12905-021-01547-3
|View full text |Cite
|
Sign up to set email alerts
|

Suicide and deliberate self-harm among women in Nepal: a scoping review

Abstract: Background Suicide is a growing public health problem globally. Suicide accounts for 70% of violent deaths among women in low and middle income countries. In Nepal suicide is the single leading cause of death among women of reproductive age. The aim of this scoping review is to explore and understand the various contexts related to vulnerability of Nepalese woman towards suicide and deliberate self-harm. Methods A scoping review based on Arksey and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
(102 reference statements)
0
5
0
1
Order By: Relevance
“…4,70 However, studies in South Asia have shown a higher proportion of married individuals among those engaging in suicidal behavior. 59,68,[71][72][73] This contrasting finding suggests that the association between marital status and suicidal behavior may be influenced by cultural, social, and economic factors specific to the South Asian region. Specifically, gender stereotyping, limited agency for women, and the expectation of fulfilling certain marital responsibilities may contribute to stress and psychological distress within marriages, potentially increasing the risk of suicidal behavior among married individuals, particularly among women.…”
Section: Implications Of the Study Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…4,70 However, studies in South Asia have shown a higher proportion of married individuals among those engaging in suicidal behavior. 59,68,[71][72][73] This contrasting finding suggests that the association between marital status and suicidal behavior may be influenced by cultural, social, and economic factors specific to the South Asian region. Specifically, gender stereotyping, limited agency for women, and the expectation of fulfilling certain marital responsibilities may contribute to stress and psychological distress within marriages, potentially increasing the risk of suicidal behavior among married individuals, particularly among women.…”
Section: Implications Of the Study Resultsmentioning
confidence: 98%
“…In many Western countries, being unmarried or divorced is often associated with a higher risk of suicidal behavior, while being married is generally considered protective 4,70 . However, studies in South Asia have shown a higher proportion of married individuals among those engaging in suicidal behavior 59,68,71–73 . This contrasting finding suggests that the association between marital status and suicidal behavior may be influenced by cultural, social, and economic factors specific to the South Asian region.…”
Section: Discussionmentioning
confidence: 99%
“…No Nepal, houve um considerável aumento na contribuição do suicídio (16%) para mortes de mulheres em idade reprodutiva, de modo que o suicídio em 2009 foi a principal causa de morte entre mulheres em idade reprodutiva 26 . Estudo mostrou que o contexto social caracterizado pelo patriarcado, pela desigualdade de gênero, pela pobreza, por normas socioculturais rígidas, relações familiares e conjugais conflituosas no Nepal contribuem para essa realidade pois tornam as mulheres vulneráveis à ideação suicida, tentativas de suicídio e automutilação 27 .…”
Section: Resultsunclassified
“…In many Western countries, being unmarried or divorced is often associated with a higher risk of suicidal behavior, while being married is generally considered protective (4,70). However, studies in South Asia have shown a higher proportion of married individuals among those engaging in suicidal behavior (59,68,(71)(72)(73). This contrasting finding suggests that the association between marital status and suicidal behavior may be influenced by cultural, social, and economic factors specific to the South Asian region.…”
Section: Implications Of the Study Resultsmentioning
confidence: 99%